Design and simulation of artificial fish lateral line. (17th January 2019) - Tang, Zhijie; Feng, Hao; Lei, Jingtao; Lu, Jiaqi; Wang, Zhen; Fu, Bin; Chen, Weiwei
Fishes can avoid colliding with obstacles and track baits depending on the lateral distributed sense nodes which can sense the pressure variances of the surrounding flow field. Fish often uses the lateral-line system as their only means for navigation, especially under poor visual conditions. This sensing mechanism provides a new perspective for researchers and engineers to build such a sensing system that could be applied to control and near field navigation for underwater robots and vehicles. In this article, a pressure-sensing-based is proposed, with 10 pressure sensors acting as lateral line and use the three-dimensional printer to print the fish structure and install the artificial lateral line on it. Through preliminary experiments and numerical simulation, we obtain the pressure sensor data. By comparing the experimental data with the numerical simulation data, it can be verified that the pressure variation of the pressure sensor in the numerical simulation data is consistent with that in the experimental data. The artificial lateral line provides a new sense to man-made underwater vehicles and marine robots, so that they can sense like fish.